2014
DOI: 10.1038/ejhg.2014.202
|View full text |Cite
|
Sign up to set email alerts
|

Five children with deletions of 1p34.3 encompassing AGO1 and AGO3

Abstract: Small RNAs (miRNA, siRNA, and piRNA) regulate gene expression through targeted destruction or translational repression of specific messenger RNA in a fundamental biological process called RNA interference (RNAi). The Argonaute proteins, which derive from a highly conserved family of genes found in almost all eukaryotes, are critical mediators of this process. Four AGO genes are present in humans, three of which (AGO 1, 3, and 4) reside in a cluster on chromosome 1p35p34. The effects of germline AGO variants or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…Recent SFARI study has identified missense mutations in miRISC proteins AGO1, TNRC6B, and CNOT3 among patients diagnosed with Autism Spectrum Disorders (Chen et al, 2019) Patients with microdeletions of chromosomal region 1p34.3 encompassing the AGO1 and AGO3 genes also show several neurodevelopmental defects (Tokita et al, 2015). Similarly, studies have also identified a crucial role of miRISC in neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 98%
“…Recent SFARI study has identified missense mutations in miRISC proteins AGO1, TNRC6B, and CNOT3 among patients diagnosed with Autism Spectrum Disorders (Chen et al, 2019) Patients with microdeletions of chromosomal region 1p34.3 encompassing the AGO1 and AGO3 genes also show several neurodevelopmental defects (Tokita et al, 2015). Similarly, studies have also identified a crucial role of miRISC in neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 98%
“…Tokita et al. (), described three individuals whose 1p34.3 deletions also encompass the SNIP1 gene (probands 1, 2, and 4). All three had a history of motor and speech delays of unknown severity; however, as mentioned previously, their deletions also included the AGO1 and AGO3 genes which have been hypothesized to be associated with developmental delays, hypotonia, and poor feeding.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have not been individuals reported with the 1p34.3p34.2 deletion reported here, that do not also encompass AGO1, AGO3, GRIK3, SLC2A1, or RIMS3 . All five of these genes have been speculated or proven to be associated with neurocognitive delays (Tokita et al., ; Takenouchi et al., ; Delisi et al., ; Vermeer et al., ; Lee et al., ; Kumar et al., ). Clinical similarities between our patient and those described in the literature include the following: intellectual disability, developmental delay, and kyphoscoliosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain magnetic resonance imaging (MRI) was performed on the two living affected members of the family (III–2 and IV–1). Array CGH‐analysis (CytoChip ISCA 4 × 180 K v1.0 BlueGnome, Cambridge, UK) and Fragile‐X genetic tests were performed on both living patients, as described previously [Cavani et al, ; Tokita et al, ].…”
Section: Methodsmentioning
confidence: 99%